Effect of neodymium:yttrium–aluminum–garnet laser and fluoride on the acid demineralization of enamel. Issue 1 (18th August 2015) - Braga, Sheila Regina Maia; de Oliveira, Elisabeth; Sobral, Maria Angela Pita
Abstract: Aim: The aim of the present study was to evaluate the protective effect of the neodymium:yttrium–aluminum–garnet (Nd:YAG) laser and acidic phosphate fluoride (APF) on enamel erosion caused by hydrochloric acid. Methods: Fifty human enamel specimens were distributed according to the following treatments ( n = 10): untreated (control), APF (1.23%) 4 min, Nd:YAG laser (100 mJ, 1 W, 10 Hz, 141.5 J/cm 2 ), APF + Nd:YAG laser, and Nd:YAG laser + APF. For 14 days the specimens were submitted to erosive challenge: 5 min in 3 mL hydrochloric acid (0.01 M, pH 2.2), rinsed with distilled water, and stored in artificial saliva for 3 h. This cycle was repeated four times per day. The calcium (Ca) loss was determined in demineralizing solution by atomic emission spectroscopy, and superficial roughness (Ra) was measured before and after the erosive challenge. Results: The mean Ca loss was (mg/L, ± standard deviation): control 12.74 ± 3.33, APF 1.71 ± 0.11, laser 1.64 ± 0.08, APF + laser 1.38 ± 0.08, and laser + APF 1.48 ± 0.07. Kruskal–Wallis test showed a significant difference between the control and other groups. APF + laser showed minor loss of Ca. After the erosive challenge, the APF + laser group showed Ra alteration. Conclusion: A significant reduction in tooth dissolution was observed after fluoride application combined with Nd:YAG irradiation.